Bureaucratic Barriers to Social Protection for Refugees and Asylum Seekers during the COVID-19 Disaster in South Africa (African Human Mobility Review, 2021)
ABSTRACTThe economic fallout of the coronavirus pandemic could be minimised by social protection instruments such as unemployment insurance and distress relief grants. This paper assesses the ability of refugees and asylum seekers to access these instruments in South Africa. In general, the bureaucratic system of asylum documentation acts as a barrier to access social protection, as exemplified by the administration of the Unemployment Insurance Fund and the Social Relief of Distress grants during the pandemic. While this problem has traditionally been articulated in terms of equality and socio-economic rights, this paper proposes that asylum administration should also be prioritised as a disaster preparedness and management infrastructure, as well as an essential service. This is to ensure refugees and asylum seekers’ need for protection is not neglected in a disaster.